Study of the normal heart size in Northwest part of Iranian population: a cadaveric study - Mohammadi, Shabnam (J Cardiovasc Thorac Res, 2016)
Introduction: The heart is in a muscular organ in the middle mediastinum. According to our knowledge, there is no standard data about the anthropologic parameters of normal Iranian hearts. Hence, the aim of the present study was to investigate the normal heart size in Iranian cadavers. Methods: In a cross-sectional study, 550 cadavers (104 female/446 male) from June 2014 to July 2015 in the Razavi Khorasan province of Iran were included in the study. After approval of the Ethical Committee, cadavers were divided into 10 groups based on age groups. Length, width, weight, chordae tendineae, papillary muscles, and heart valves were measured using vernier caliper. Finally, data were analyzed using SPSS software. Results: The mean values of the demographic data were as follows: age= 42.12 ± 21.34 years; weight = 60.38 ± 15.32 kg; height = 158.14 ± 23.77 cm; and BMI = 24.66 ± 17.60 kg/m(2). The mean values of the heart length, width, chordae tendineae, pupillary muscles, weight, and index of the heart were 11.41 ± 2.15 cm, 8.21 ± 4.38 cm, 19.41 ± 6.70, 5.74 ± 1.96, 247.78 ± 62.27 grams, and 5.74 ± 1.96, respectively. In addition, the circumference of the tricuspid valve, circumference of the mitral valves, and tricuspid and mitral areas were 8.80 ± 1.11 cm, 9.43 ± 1.44 cm, 4.11 ± 0.71 cm(2), and 4.50 ± 0.90 cm(2), respectively. Conclusion: Mean values of the heart’s length and width was similar to previous reports from western population. The circumference of the tricuspid valve was less than the textbook’s data, while circumference of the mitral valves was more than it. The study findings provide valuable information about standard data of the heart in the Iranian population, which is useful for surgeons as well as anthropologists. However, multi-center studies with a larger sample size are required to complete data about anatomical characteristics of normal hearts.